The Effect of Range of Motion Exercise on Extremity Muscle Strength in Non-Hemoragic Stroke Patients - Jannah, Zulfa Fairuz; Kristinawati, Beti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Blockage of a blood vessel causes a cut in the supply of oxygen and nutrients resulting in damage to brain tissue. Stroke symptoms usually appear suddenly with loss of muscle strength in one or both extremities. One intervention to increase muscle strength in stroke patients is Range Of Motion exercise. The purpose of this case study is to determine the effect of Range Of Motion exercises on muscle strength in patients with non-hemorrhagic stroke disease. The method in this case study is to interview the patient's family about the disease and health before entering the hospital and assess muscle strength before range of motion exercises are carried out. Data was collected in this study by looking at medical records and interviewing the patient's family, and The method used is a case study in patients with muscle weakness in the lower and upper extremities and given range of motion exercises and evaluated the increase in muscle strength after implementation. The results of the case study after the intervention of Range Of Motion exercises there was an increase in muscle strength in non-hemorrhagic stroke patients. In the results of this case study there was an increase in muscle strength after the intervention, so that Range Of Motion exercises were considered very effective.